2011
DOI: 10.1177/0165551511407141
|View full text |Cite
|
Sign up to set email alerts
|

A study of interdisciplinarity in information science: using direct citation and co-authorship analysis

Abstract: This study uses two bibliometric methods, direct citation and co-authorship, to investigate the interdisciplinary changes in information sciences during 1978—2007. The disciplines of references and co-authors from five information science journals were analysed. Furthermore, Brillouin’s Index was adopted to measure the degree of interdisciplinarity. The study revealed that information science researchers have cited the publications of library and information science (LIS) most frequently. The co-authors of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 17 publications
1
50
0
7
Order By: Relevance
“…Second, we used Brillouin's index (Brillouin, 1956) to assess the overall interdisciplinarity of each corpus. This index is used as a measure of population diversity in the field of ecology (e.g., Peet, 1975), and has been used to assess interdisciplinarity in other research fields (e.g., Huang & Chang, 2011;Steele & Stier, 2000). We chose to use Brillouin's index rather than a measure of sample diversity because of the exhaustive nature of our literature search, suggesting that our corpus is more accurately characterized as a population (i.e., all empirical MOOC research published in English in the time period described) than a sample (i.e., a portion of the research fulfilling those criteria).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we used Brillouin's index (Brillouin, 1956) to assess the overall interdisciplinarity of each corpus. This index is used as a measure of population diversity in the field of ecology (e.g., Peet, 1975), and has been used to assess interdisciplinarity in other research fields (e.g., Huang & Chang, 2011;Steele & Stier, 2000). We chose to use Brillouin's index rather than a measure of sample diversity because of the exhaustive nature of our literature search, suggesting that our corpus is more accurately characterized as a population (i.e., all empirical MOOC research published in English in the time period described) than a sample (i.e., a portion of the research fulfilling those criteria).…”
Section: Discussionmentioning
confidence: 99%
“…There has also been research examining how the level of interdisciplinarity in a field changes over time. For instance, Huang and Chang (2011) demonstrated that research in Information Science has become increasingly interdisciplinary over the course of three decades. If interdisciplinarity does allow for a more rounded perspective on research problems, such changes may indicate a field's increasing sophistication and complexity -particularly if this field is relatively nascent.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (2005) adopted the social network measures of degree, closeness, betweenness, and eigenvector centrality to explore individuals' positions in a given co-authorship network. Similar to many of the studies on co-authorship network (Ding-quan et al 2009;Huang and Chang 2011), in this study we consider a co-authorship network of a specific research field, and analyze this network by applying known statistical and network measures. However, our approach of analysis to co-authorship network is abstract, and is able to answer scientific queries regarding trend of evolutionary dynamics and proximity of collaborative efficiency of scientific collaborations.…”
Section: Introductionmentioning
confidence: 99%
“…Huang & Chang (2011) investigated the interdisciplinary changes in the IS field in the period by analyzing five information science journals.…”
Section: Society For Information Science and Technologymentioning
confidence: 99%